Pengaruh Kualitas Pengendalian Intern Terhadap Efesiensi Operasional Pada Bank Sumut KCP Sei Sikambing Medan - Hendra Saputra; Dwihar Fitriani (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the influence of Internal Control Quality on Operational Efficiency. The population in this research is the company PT Bank Sumut in 2021-2023. Data was taken from the financial reports of selected companies by sampling using the questionnaire distribution method. The approach used in this research is quantitative associative analysis. The data analysis technique uses simple linear regression analysis. The research results show that the Quality of Internal Control has an impact on Operational Efficiency.